2015
DOI: 10.1111/eva.12270
|View full text |Cite
|
Sign up to set email alerts
|

Genomic basis of the differences between cider and dessert apple varieties

Abstract: Unraveling the genomic processes at play during variety diversification is of fundamental interest for understanding evolution, but also of applied interest in crop science. It can indeed provide knowledge on the genetic bases of traits for crop improvement and germplasm diversity management. Apple is one of the most important fruit crops in temperate regions, having both great economic and cultural values. Sweet dessert apples are used for direct consumption, while bitter cider apples are used to produce cide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 64 publications
2
26
1
Order By: Relevance
“…The results are also consistent with the very weak differentiation between dessert and cider apples, as already shown by Cornille et al (2012) on a partially redundant set of accessions. A recent study by our group also underlined the difficulties in finding loci involved in the dessert vs. cider differentiation at the genome level (Leforestier et al 2015).…”
Section: Genetic Diversity and Structure Observed In The French Applementioning
confidence: 98%
See 1 more Smart Citation
“…The results are also consistent with the very weak differentiation between dessert and cider apples, as already shown by Cornille et al (2012) on a partially redundant set of accessions. A recent study by our group also underlined the difficulties in finding loci involved in the dessert vs. cider differentiation at the genome level (Leforestier et al 2015).…”
Section: Genetic Diversity and Structure Observed In The French Applementioning
confidence: 98%
“…These core collections are already used for various goals as exemplified by the study of the differentiation between dessert and cider apples (Leforestier et al 2015). The dessert apple core collection is also currently being phenotyped for various agronomical traits and SNP genotyped within the framework of the European project FruitBreedomics (Laurens et al 2010).…”
Section: Definition Of Inra Diploid Core Collections For Association mentioning
confidence: 99%
“…An r 2 below 0.2 within 100 kbp was in fact reported by Leforestier et al . () in two core collections of unrelated accessions of dessert and cider apples, while Kumar et al . () reported an r ² below 0.13 within 100 kbp in a diverse population of apple accessions.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported the use of the two medium-density Infinium â arrays for the generation of a number of saturated genetic linkage maps and QTL detection (Antanaviciute et al, 2012;Clark et al, 2014;Falginella et al, 2015) in bi-parental full-sib families, for pedigree-based analysis (PBA) on multiple pedigreed families (Guan et al, 2015;Allard et al, 2016) or for GWA analysis in a family-based design (Kumar et al, 2013). However, GWA studies using the 8K SNP array in collections of unre-lated apple accessions (Kumar et al, 2014;Leforestier et al, 2015) highlighted the limitations of the arrays available to date, which provide a low density of markers for GWA studies as LD decays quite quickly in apple. An r 2 below 0.2 within 100 kbp was in fact reported by Leforestier et al (2015) in two core collections of unrelated accessions of dessert and cider apples, while Kumar et al (2014) reported an r² below 0.13 within 100 kbp in a diverse population of apple accessions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation